PENGARUH KOMITMEN, KOMUNIKASI, DAN KERJASAMA TIM UNTUK MENINGKATKAN KINERJA KARYAWAN PADA DREAM OF AVENTUS HOTEL KUTA - I Kadek Supendi Urya Aras Wirawan; I Made Hedy Wartana (Universitas Triatma Mulya, 2026)
This study aims to determine the influence of commitment, communication, and teamwork on improving employee performance at Dream Of Aventus Hotel Kuta. The research employs a descriptive quantitative method. The sampling technique used is saturated sampling or census. The sample in this study consists of all employees at Dream Of Aventus Hotel Kuta, with a total of 62 respondents. The data were collected using a questionnaire, and the analysis was conducted using multiple linear regression with SPSS Statistics 27. The results show that (1) commitment has a positive and significant effect on employee performance at Dream Of Aventus Hotel Kuta, (2) communication has a positive and significant effect on employee performance at Dream Of Aventus Hotel Kuta, and (3) teamwork has a positive and significant effect on employee performance at Dream Of Aventus Hotel Kuta. Based on these findings, the researcher suggests that the company increase employee commitment by providing bonuses and recognition for their contributions, as well as developing mentoring programs to help employees improve their skills. Furthermore, the company can enhance communication by promoting a positive and friendly work culture through employee training and development, and by using social media to facilitate better communication among colleagues. Finally, the company can strengthen teamwork by building a solid team structure and providing relevant training and skill development that align with team needs.